Flame-retardant binder, electrode slurry, electrode, battery and electric device

By using a flame retardant adhesive combined with CMC and CR, the problem of insufficient flame retardant adhesive of lithium-ion battery auxiliary material adhesive is solved, and the circulation performance and safety of the battery are improved.

CN119799200APending Publication Date: 2025-04-11GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411683896.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The flame retardant safety of lithium-ion batteries is mainly concentrated in the main material electrolyte and separator. The flame retardant research on the auxiliary material adhesive is relatively lacking, resulting in the risk of fire and explosion during use of the battery.

Method used

A flame retardant adhesive combined with sodium carboxymethylcellulose (CMC) and neoprene (CR) is used to form a CMC@CR adhesive through physical blending, which improves the stability of the electrode structure and enhances the cycle performance and flame retardant performance of the battery.

Benefits of technology

It improves the stability of the electrode structure, avoids the problem of cracks in the adhesive, and significantly improves the circulation performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148984420000031
    Figure BDA0005148984420000031
  • Figure BDA0005148984420000041
    Figure BDA0005148984420000041
  • Figure BDA0005148984420000051
    Figure BDA0005148984420000051
Patent Text Reader

Abstract

The invention relates to the field of new energy batteries, and discloses a flame-retardant binder, electrode slurry, an electrode, a battery and an electric device. According to the present invention, the new energy battery auxiliary material binder is improved, the sodium carboxymethyl cellulose (CMC) is adopted as the binder substrate material, and the physical blending of the chloroprene rubber (CR) is performed so as to form the binder CMC-CR, such that the good adhesion ability is provided, and the certain flame retardation effect is provided. Meanwhile, an electrode prepared by using the flame-retardant binder is higher in structural stability, the defect that a single binder CMC (Carboxy Methylated Cellulose) is easy to crack is avoided, and an assembled battery has more excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy batteries, and in particular to a flame retardant binder, electrode slurry, electrode, battery and electrical device. Background Art

[0002] As the core of the current new energy technology field, lithium-ion batteries have the advantages of high energy density, high output voltage, long cycle life, and low environmental pollution. They are not only widely used in various small electronic devices, but also have been rapidly developed in power vehicles and energy storage technology. With the rapid development of power energy storage technology, reports of fires and even explosions caused by lithium-ion batteries have become common. The safety issues of lithium-ion batteries have attracted widespread attention and are currently the main obstacle to the industrial upgrading of lithium-ion batteries in the fields of power and large-scale energy storage.

[0003] In order to better avoid this phenomenon, the use of flame retardant additives came into being. At present, the flame retardant safety of lithium-ion batteries mainly focuses on the improvement of the flame retardancy of the main material electrolyte and diaphragm, while the research on the flame retardancy of the auxiliary material binder is basically in a blank stage. Summary of the invention

[0004] In view of this, the purpose of the present application is to provide a flame retardant adhesive, which not only has better flame retardant properties but also has higher bonding strength;

[0005] Another object of the present application is to provide an electrode slurry, an electrode, a battery and an electrical device based on the above-mentioned flame retardant binder, so that the assembled electrode structure is more stable and cracking is avoided, while the cycle performance of the battery is significantly improved.

[0006] In order to solve the above technical problems / achieve the above objectives or at least partially solve the above technical problems / achieve the above objectives, as a first aspect of the present application, a flame retardant adhesive is provided, comprising sodium carboxymethyl cellulose (CMC) and chloroprene rubber (CR).

[0007] Optionally, the mass ratio of the sodium carboxymethyl cellulose to the chloroprene rubber is (0.27-0.375):(0.1-0.3).

[0008] As a second aspect of the present application, an electrode slurry is provided, comprising an active material, a conductive agent, a solvent, and the flame retardant binder described in the present application.

[0009] Optionally, based on weight, the composition includes 16-19 parts of active material, 0.4-2 parts of conductive agent, 0.27-0.375 parts of sodium carboxymethyl cellulose, 0.1-0.3 parts of chloroprene rubber, and 1-6 parts of solvent.

[0010] Further optionally, the electrode slurry is a negative electrode slurry.

[0011] As a third aspect of the present application, a method for preparing the electrode slurry is provided, comprising:

[0012] The active material, the conductive agent and sodium carboxymethyl cellulose are pre-grinded according to the ratio, and then a solvent is added to continue grinding and mixing, and chloroprene rubber is added to continue grinding and slurrying to obtain the electrode slurry.

[0013] As a fourth aspect of the present application, an electrode plate is provided, comprising a current collector and an active material layer located on the surface of the current collector, wherein the active material layer is formed by coating the current collector with the electrode slurry described in the present application and drying it.

[0014] As a fifth aspect of the present application, a battery is provided, comprising the electrode, counter electrode, separator and electrolyte described in the present application.

[0015] Optionally, the battery comprises a lithium-ion battery.

[0016] As a sixth aspect of the present application, an electrical device is provided, comprising the battery described in the present application, wherein the battery provides electrical energy for the electrical device.

[0017] This application improves the binder of auxiliary materials for new energy batteries, uses sodium carboxymethyl cellulose (CMC) as the binder base material, and forms a binder CMC@CR through physical blending with chloroprene rubber (CR). The binder not only has good adhesion but also has a certain flame retardant effect. At the same time, the electrode structure prepared using the flame retardant binder is more stable, avoiding the defect of single binder CMC being prone to cracks, and the assembled battery has better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.

[0019] Figure 1 The figure shows the comparison results of the cycle performance of the sample batteries of Example 1, Comparative Example 1 and Comparative Example 2 at 0.2C; CMC@CR represents the result of Example 1, CMC represents the result of Comparative Example 1, and CR represents the result of Comparative Example 2;

[0020] Figure 2 The figure shows the 180° peeling test comparison results of the electrode sheets of the samples of Example 1, Comparative Example 1 and Comparative Example 2; CMC@CR represents the result of Example 1, CMC represents the result of Comparative Example 1, and CR represents the result of Comparative Example 2;

[0021] Figure 3 Shown are the SEM results of the electrode surface morphology of the battery samples of Example 1, Comparative Example 1 and Comparative Example 2 after cycling; (a) is the morphology of Comparative Example 1 before cycling, (b) is the morphology of Comparative Example 2 before cycling, (c) is the morphology of Example 1 before cycling, (d) is the surface morphology of Comparative Example 1 after 100 cycles, (e) is the surface morphology of Comparative Example 2 after 100 cycles, and (f) is the surface morphology of Example 1 after 100 cycles. DETAILED DESCRIPTION

[0022] The present application discloses a flame retardant binder and an electrode slurry, an electrode, a battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0023] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.

[0024] As a binder frequently used in new energy batteries, CMC has high viscosity, which can increase the viscosity of the slurry and prevent the slurry from settling; it also contains rich carboxyl functional groups, has good adhesion to the current collector metal foil, and has conductivity; at the same time, it has good dispersibility for the negative electrode. However, CMC also has obvious disadvantages, such as brittleness, poor elasticity, and poor flame retardant effect. If all CMCs are selected as binders, the negative electrode collapses during baking, rolling and cutting, and serious powder loss will occur. The pole piece may crack during charging and discharging, which directly affects the cycle performance and safety of the battery. Therefore, in the first aspect of the present application, a flame retardant binder is provided, including sodium carboxymethyl cellulose (CMC) and chloroprene rubber (CR). The present application finds that the composite use of CR and CMC can improve the brittleness of CMC to a certain extent, improve the stability of adhesion and the structural stability of the electrode, and improve the cycle performance of the battery. In addition, the addition of CR also improves the flame retardant properties of the composite binder CMC@CR and improves the safety of battery use.

[0025] In certain embodiments of the present application, the mass ratio of sodium carboxymethyl cellulose to chloroprene rubber is (0.27-0.375):(0.1-0.3).

[0026] In a second aspect of the present application, an electrode slurry is provided, comprising an active material, a conductive agent, a solvent, and the flame retardant binder described in the present application.

[0027] In certain embodiments of the present application, the electrode slurry includes, by weight, 16-19 parts of active material, 0.4-2 parts of conductive agent, 0.27-0.375 parts of sodium carboxymethyl cellulose, 0.1-0.3 parts of chloroprene rubber, and 1-6 parts of solvent.

[0028] In some other embodiments of the present application, the solvent includes water and N-methylpyrrolidone (NMP), and the mass ratio of the two is (0.5-3):(0.5-3).

[0029] In some other embodiments of the present application, the electrode slurry is a negative electrode slurry, and its weight ratio is shown in Table 1 below;

[0030] Table 1

[0031]

[0032]

[0033] In certain embodiments of the present application, the negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, silicon carbon, and nano silicon particles. The conductive agent includes one or more of carbon black conductive agents, carbon nanotube conductive agents, conductive graphite conductive agents, graphene conductive agents, and carbon fiber conductive agents. Among them, carbon black conductive agents include conductive carbon black SP, Ketjen black, and acetylene black.

[0034] In the third aspect of the present application, a method for preparing the electrode slurry is provided, comprising:

[0035] The active material, the conductive agent and sodium carboxymethyl cellulose are pre-grinded according to the ratio, and then a solvent is added to continue grinding and mixing, and chloroprene rubber is added to continue grinding and slurrying to obtain the electrode slurry.

[0036] In certain embodiments of the present application, the pre-milling, milling and mixing, and milling pulping are all performed by ball milling. In other embodiments of the present application, the pre-milling time is 10-30 min, and the ball milling speed is 50-150 rpm / min. The ball milling mixing time is 20-45 min, and the ball milling speed is 200-500 rpm / min. The ball milling pulping time is 15-30 min, and the ball milling speed is 200-500 rpm / min.

[0037] In certain embodiments of the present application, the CMC is prepared into a CMC aqueous solution with a solid content of 1.5%; the CR is prepared into a CR aqueous solution with a solid content of 50.0%.

[0038] In certain embodiments of the present application, the solvent includes NMP and deionized water, which need to be mixed and added in a mass ratio of 1:1, and the amount of the mixed solvent added is adjusted according to the rheological degree of the slurry after pre-milling (which can be judged by observing the fluidity of the ball milling beads in the slurry).

[0039] In a fourth aspect of the present application, an electrode plate is provided, comprising a current collector and an active material layer located on the surface of the current collector, wherein the active material layer is formed by coating the current collector with the electrode slurry described in the present application and drying it.

[0040] In certain embodiments of the present application, the electrode plate is a negative electrode plate, and the current collector is made of a metal foil with good conductivity, such as aluminum foil, copper foil, etc.;

[0041] In a fifth aspect of the present application, a battery is provided, comprising the electrode, counter electrode, separator and electrolyte described in the present application.

[0042] In some embodiments of the present application, the battery includes a lithium-ion battery, such as a button battery, a soft-pack battery, a square-shell battery, a cylindrical battery, etc.; in some other embodiments of the present application, the lithium-ion battery is a button battery, the electrode in the present application is a negative electrode, the counter electrode is a metal lithium sheet, the diaphragm is Celgard 2400, and the electrolyte is a lithium hexafluorophosphate electrolyte.

[0043] In the sixth aspect of the present application, an electric device is provided, comprising the battery described in the present application, wherein the battery provides electric energy for the electric device. The electric device includes but is not limited to electronic devices, electric vehicles, and the like, such as household appliances, electric vehicles, aircraft, balancing vehicles, electric bicycles, electric tricycles, computers, mobile phones, tablet computers, robots, and the like.

[0044] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0045] The following is a further description of a flame retardant binder, electrode slurry, electrode, battery and electrical device provided in the present application.

[0046] Embodiment 1:

[0047] (1) Weight ratio of negative electrode slurry

[0048] Table 2

[0049]

[0050] (2) Negative electrode slurry preparation method

[0051] The nano-silicon particle negative electrode active material, acetylene black and CMC solution were weighed according to the mass and placed in a ball mill, and 2 large and 4 small ball mill beads (the large one had a diameter of 12 mm and the small one had a diameter of 6 mm) were added and pre-milled in a ball mill at a speed of 100 rpm / min for 15 min; then a mixture of 2.0 g NMP and deionized water was added, and the mixture was fully mixed by ball milling at a speed of 300 rpm / min for 40 min; finally, 0.4 g CR solution was added at this speed and ball milling was continued for 20 min to obtain a lithium-ion battery negative electrode slurry.

[0052] (3) Snap-on assembly

[0053] The negative electrode slurry obtained by ball milling was coated on copper foil, and cut into circular electrode pieces with a diameter of 12 mm after vacuum drying at 105°C. After drying, the mass of the electrode pieces was accurately weighed and the active material content was calculated. The button cell was assembled in a vacuum glove box using a metal lithium sheet as the counter electrode and Celgard 2400 as the separator.

[0054] Embodiment 2:

[0055] The process is similar to that of Example 1, except that the ball milling speed after adding the CR binder solution is changed to 500 rpm / min and the milling time is changed to 30 min.

[0056] Embodiment 3:

[0057] The process is similar to that of Example 1, except that the negative electrode active material is changed to artificial graphite.

[0058] Embodiment 4:

[0059] The process is similar to that of Example 1, except that the conductive agent is replaced with Ketjen black.

[0060] Comparative Example 1:

[0061] Referring to the process of Comparative Example 1, the difference is that the preparation of the negative electrode slurry only requires the addition of a single CMC binder solution with a mass of 33.3 g (0.5 g CMC), and the final process of adding the CR solution is removed.

[0062] Comparative Example 2

[0063] Referring to the process of Comparative Example 1, the difference is that the preparation of the negative electrode slurry only requires changing the process of adding CMC solution to adding CR solution, the added mass is 1.0g (0.5gCR), and removing the last process of adding CR solution.

[0064] Experimental example:

[0065] (1) Test method

[0066] Battery performance test: Charge and discharge tests were carried out on a Xinwei tester. Test conditions: 0.2C, 25℃, and the charge and discharge cut-off voltage was 0.005V-1.5V.

[0067] Characterization test of the electrode: the electrode after coating and drying before cycling is cut into small pieces of 4cm*2cm for 180° peeling test; the battery after cycling is disassembled and subjected to scanning electron microscope test.

[0068] Flame retardant performance test: The binders of the embodiments and comparative examples were subjected to an oxygen index flame retardant performance test.

[0069] (2) Experimental results

[0070] like Figure 1 As shown in the cycle performance, it can be seen that the cycle performance of the silicon negative electrode of Example 1 is significantly better than that of the silicon negative electrode of Comparative Example 1 and Comparative Example 2. Specifically, the silicon negative electrode of Example 1 has stable cycle performance and slow capacity decay, while the capacity decay of the silicon negative electrode of the comparative example is very rapid and the cycle performance is extremely poor, among which the cycle performance of Comparative Example 1 is the worst.

[0071] like Figure 2 As shown in the 180° peel test, it can be seen that the average peeling force of the silicon negative electrode sheet of Example 1 ( Figure 1 The curve corresponding to CMC@CR is about 2.23N) which is much higher than the average peeling force of the silicon negative electrode sheet in the comparative example ( Figure 1 The curve corresponding to CMC is about 0.22N; the curve corresponding to CR is about 0.12N), indicating that the bonding strength of CMC@CR is much higher than that of CMC and CR, which also indirectly confirms that Example 1 has better cycle performance than the comparative example.

[0072] like Figure 3 The graph shows the electrode surface morphology of the silicon negative electrode of Example 1 (CMC@CR) and the silicon negative electrode of Comparative Example 1 (CMC) and Comparative Example 2 (CR) before and after 100 cycles. Figure 3 (a) shows the morphology of CMC before cycling. Figure 3 (d) shows the surface morphology of CMC after 100 cycles; Figure 3 (b) shows the morphology before CR cycle. Figure 3 (e) shows the surface morphology after 100 CR cycles; Figure 3 (c) shows the morphology of CMC@CR before cycling. Figure 3 (f) in the figure is the surface morphology of CMC@CR after 100 cycles. It can be seen that there are some tiny cracks on the surface of the silicon negative electrode of the comparative examples (CMC and CR) before the cycle. For CMC, this is due to the rigidity of CMC itself, which causes certain cracking of the electrode during baking, rolling and cutting. After the cycle, the cracks become larger and even powder falls off due to the expansion of the silicon particles. For CR, it is because of its relatively weak adhesion that it is difficult to limit the expansion of silicon particles, resulting in cracking of the electrode. The surface of the silicon negative electrode of Example 1 effectively alleviates the rigidity of CMC due to the addition of CR, so that the electrode remains smooth before and after the cycle, without obvious structural changes. This also further shows that the cycle performance of the silicon negative electrode of Example 1 is significantly better than that of Comparative Examples 1 and 2.

[0073] As can be seen from Table 3 below, compared with CMC and CR, the electrode binder of Example 1 has better flame retardancy than any single binder due to the combination of CR and CMC, thereby ensuring that the lithium-ion battery using the electrode binder has better safety and other properties.

[0074] Table 3

[0075] Binder LOI value / % CMC@CR 27.4 CMC 19.5 CR 25.8

[0076] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A flame retardant adhesive, characterized in that: Includes sodium carboxymethyl cellulose and neoprene.

2. The flame retardant adhesive according to claim 1, characterized in that: The mass ratio of the sodium carboxymethyl cellulose to the chloroprene rubber is (0.27-0.375):(0.1-0.3).

3. An electrode slurry, characterized in that: The invention comprises an active material, a conductive agent, a solvent, and the flame retardant adhesive according to claim 1 or 2.

4. The electrode slurry according to claim 3, characterized in that: In parts by weight, it comprises 16-19 parts of active materials, 0.4-2 parts of conductive agents, 0.27-0.375 parts of sodium carboxymethyl cellulose, 0.1-0.3 parts of chloroprene rubber, and 1-6 parts of solvents.

5. The electrode slurry according to claim 3 or 4, characterized in that: The electrode slurry is a negative electrode slurry.

6. The method for preparing the electrode slurry according to claim 3, characterized in that: include: The active material, the conductive agent and sodium carboxymethyl cellulose are pre-grinded according to the ratio, and then a solvent is added to continue grinding and mixing, and chloroprene rubber is added to continue grinding and slurrying to obtain the electrode slurry.

7. An electrode plate, characterized in that: It comprises a current collector and an active material layer located on the surface of the current collector, wherein the active material layer is formed by coating the current collector with the electrode slurry according to any one of claims 3 to 5 and drying it.

8. A battery, characterized in that: The method comprises the electrode according to claim 7, a counter electrode, a separator and an electrolyte.

9. The battery according to claim 8, characterized in that The battery comprises a lithium ion battery.

10. An electrical device, characterized in that: The battery comprises the battery as claimed in claim 8 or 9, wherein the battery provides electrical energy for the electrical device.

Citation Information

Cited By

  • Preparation method of high-flexibility water-soluble high-viscosity CMC material

    CN120647781A

  • High-flexibility water-soluble high-viscosity CMC material and application thereof

    CN120682384A